AN APPRAISAL OF END‐OF‐LIFE CARE IN PERSONS WITH CHRONIC KIDNEY DISEASE DYING IN HOSPITAL WARDS. Issue 1 (19th November 2014) - Noble, Helen; Brown, Joan; Shields, Joanne; Fogarty, Damian; Maxwell, Alexander P.
SUMMARY Aim To review end‐of‐life care provided by renal healthcare professionals to hospital in‐patients with chronic kidney disease, and their carers, over a 12‐month period in Northern Ireland. Methods Retrospective review of 100 patients. Results Mean age at death was 72 years (19–95) and 56% were male. Eighty three percent of patients had a 'Not For Attempted Resuscitation' order during their last admission and this was implemented in 42%. Less than 20% of all patients died in a hospital ward. No patients had an advanced care plan, although 42% had commenced the Liverpool Care Pathway for the Dying Patient. Patients suffered excessive end‐of‐life symptoms. In addition, there was limited documentation of carer involvement and carer needs were not formally assessed. Conclusion End‐of‐life care for patients with advanced chronic renal disease can be enhanced. There is significant variation in the recording of discussions regarding impending death and little preparation. There is poor recording of the patients' wishes regarding death. Those with declining functional status, including those frequently admitted to hospital require holistic assessment regarding end‐of‐life needs. More effective communication between the patient, family and multi‐professional team is required for patients who are dying and those caring for them.